Let’s air our dirty laundry - Sicroff, Seth (Himalayan Journal of Sciences, 2006)
The truth won’t outCorruption and incompetence would not suffice to cripple development if scientists and developers were not afraid to blow the whistle and expose them. But it seems that the only way to protect your job in this little gossipy country is to protect the egos and reputations of those who are screwing up. Question: How can we put an end to self-censorshipHimalayan Journal of Sciences Vol.2(3) 2004 p9The full text is of this article is available at the Himalayan Journal of Sciences website